Bilinguals benefit from semantic context while perceiving speech in noise in both of their languages: Electrophysiological evidence from the N400 ERP. Issue 2 (5th March 2021) - Coulter, Kristina; Gilbert, Annie C.; Kousaie, Shanna; Baum, Shari; Gracco, Vincent L.; Klein, Denise; Titone, Debra; Phillips, Natalie A.
Abstract: Although bilinguals benefit from semantic context while perceiving speech-in-noise in their native language (L1), the extent to which bilinguals benefit from semantic context in their second language (L2) is unclear. Here, 57 highly proficient English–French/French–English bilinguals, who varied in L2 age of acquisition, performed a speech-perception-in-noise task in both languages while event-related brain potentials were recorded. Participants listened to and repeated the final word of sentences high or low in semantic constraint, in quiet and with a multi-talker babble mask. Overall, our findings indicate that bilinguals do benefit from semantic context while perceiving speech-in-noise in both their languages. Simultaneous bilinguals showed evidence of processing semantic context similarly to monolinguals. Early sequential bilinguals recruited additional neural resources, suggesting more effective use of semantic context in L2, compared to late bilinguals. Semantic context use was not associated with bilingual language experience or working memory.